Privatization in Transition Economies: Case Study of Poland - Ryszard Rapacki; Susan Johnston Linz (ZBW - Leibniz Information Centre for Economics; ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1992)
Contrary to expectations and announcements of policy makers in transition economies, privatization has taken longer than originally planned. This paper analyzes the institutional and behavioral factors that compound systemic barriers to privatization and thus transition from a centrally planned to a market economy. Part I describes the command economy legacy transition economies must overcome while initiating the structural transformation required to introduce a market economy. Part II presents preliminary results from Poland's privatization experience. Part III identifies the anticipated and unanticipated institutional and behavioral barriers to privatization in Poland. Part IV offers several lessons for other transition economies regarding the process and pace of privatization.
Conference: Southern Conference on Slavic Studies, Jacksonville, March 26-28, 1992; Additional information: Paper prepared for the Southern Conference on Slavic Studies, Jacksonville, March 26-28, 1992.
Keywords: p2; p3; 330; privatization; transition; privatization; transition countries